Tracking plasmodium knowlesi through fecal DNA for monitoring zoonotic transmission in wild macaques across southeast and south asia - Wannigama, Dhammika Leshan; Amarasiri, Mohan; Phattharapornjaroen, Phatthranit; Hurst, Cameron; Modchang, Charin; Cynthia, Bernadina; Miyanaga, Kazuhiko; Cui, Longzhu; Fernandez, Stefan; Melhem, Nada M.; Luk-in, Sirirat; Singer, Andrew C.; et al. (Journal of Infectious Diseases, 2026)
We conducted the noninvasive surveillance of Plasmodium knowlesi in wild macaques using 4752 fecal samples collected across 9 endemic countries. Parasite DNA was detected in 390 samples (8.2%), with positivity rates ranging from 1.4% to 18.4%. This provides the first field-based evidence that P. knowlesi DNA in feces shed by macaques and present under natural conditions can be detected. These findings validate fecal sampling as a practical and scalable tool for tracking zoonotic-malaria. The results support integration into forest-runoff and rural wastewater surveillance systems, offering new opportunities for early detection of pathogens and environmental monitoring at the human-wildlife interface. This study validates noninvasive fecal sampling for tracking Plasmodium knowlesi in wild macaques, providing a scalable tool for early pathogen detection and environmental malaria surveillance.
Keywords: environmental surveillance; fecal surveillance; macaque; Plasmodium knowlesi; zoonosis